Cultural Continuity and Identity Formation: A Study of the Gopali Community in Makawanpur District, Nepal - Budhathoki, Drona; Aryal, Uttam (International Research Journal of MMC, 2025)
Cultural continuity enables communities to sustain identity, heritage, and traditional knowledge across generations, fostering social cohesion, resilience, and intergenerational solidarity. It protects indigenous identities, preserves cultural practices amid change, and allows adaptation while maintaining foundational cultural values. The chief objectives of this study is to examine the indigenous culture of the Gopali Newar community in Kunchhal Village, Ward No. 1, Thaha Municipality, Makwanpur District, and to investigate the efforts made to preserve and sustain its continuity. This study used a descriptive research design to explore the Gopali Newar community’s identity and its sustainable cultural heritage preservation, employing purposive sampling for interviews, participant observation, and focus group discussions to gather intergenerational perspectives and contextually rich, relevant data on cultural practices. In conclusion, the study of the Gopali Newar community of Kunchhal Village highlights how cultural preservation, identity formation, and social continuity are maintained through unique practices, language, rituals, and architecture. Despite pressures from modernization and socio-economic changes, the community actively safeguards its tangible and intangible heritage, fostering intergenerational cohesion, reinforcing collective identity, and demonstrating the vital role of community agency in sustaining cultural persistence. This research is significant as it documents the Gopali Newar community’s unique cultural practices, language, rituals, and heritage, highlighting strategies for sustainable preservation. It informs anthropological understanding, supports minority cultural continuity, and provides insights for policy interventions promoting social cohesion and resilience.